Rozwiązanie:
[tex]f(x)=\frac{x^{2}}{x-4}[/tex]
Wyznaczamy dziedzinę:
[tex]D: x-4\neq 0\\x\neq 4[/tex]
Obliczamy pochodną:
[tex]f'(x)=\frac{2x(x-4)-x^{2}}{(x-4)^[2}} =\frac{2x^{2}-8x-x^{2}}{(x-4)^{2}} =\frac{x^{2}-8x}{(x-4)^{2}}\\D:x-4\neq 0\\x\neq 4[/tex]
Wyznaczamy jej miejsca zerowe:
[tex]f'(x)=0 \iff x^{2}-8x=0\\x(x-8)=0\\x=0 \vee x=8[/tex]
Szkicujemy symboliczny wykres pochodnej (załącznik) i odczytujemy:
[tex]f'(x)>0 \ dla \ x \in(-\infty,0) \cup (8,\infty)\\f'(x)=0 \ dla \ x \in [0,8]\\f'(x)<0 \ dla \ x \in (0,4) \cup (4,8)[/tex]
Stąd:
[tex]f(x)[/tex] rośnie dla [tex]x \in(-\infty,0> \cup <8,\infty)[/tex]
[tex]f(x)[/tex] maleje dla [tex]x \in <0,4) \cup (4,8>[/tex]